Relationship between Phytoplankton and Chlorophyll-a Abundance in the Outer Bay of Bangka Island - Febriyanti, Mega; Anggraeni, Anggraeni; Akhrianti, Irma (Jurnal Ilmiah Platax, 2023)
Kelabat Luar Bay is located in the north of Bangka Island, which juts out into the open sea, making this bay have a number of fisheries activities, and mining activities, especially floating unconventional mines (TI) managed by the local community. The research aims to identify phytoplankton species and analyze ecological indices as well as the relationship of physical and chemical factors to phytoplankton and chlorophyll concentration in the waters of Kelabat Luar Bay. Determination of the location of this study using a purposive sampling method. Sampling was conducted perpendicular to the sea (horizontal) by setting three sampling points (replicates) at each station with a distance of 0, 1, and 2 km. Based on the results of the study, the most common phytoplankton species found were Bacillariophyceae class of 11 species with a total of 278 individuals, Cyanophyceae 1 species with a total of 2 individuals, Chrysophyceae class of 1 species with a total of 11 individuals and Dinophyceae class of 2 species with a total of 16 individuals. The type of phytoplankton that has the highest number of individuals is Rhizosolenia robusta which totals 38 individuals. Chlorophyll-a concentration ranges between 0.0634 - 0.3014 mg/L. The phytoplankton diversity index in the waters of Kelabat Luar Bay is in the medium category (1.881-2.204), the uniformity index is high (0.880-0.957) and the dominance index is low (0.116-0.172). Physical parameters of water chemistry that affect the relationship of phytoplankton and chlorophyll include temperature, pH, brightness, and salinity. Keywords: phytoplankton; chlorophyll-a; Kelabat Bay. Abstrak Teluk Kelabat Luar terletak disebelah utara Pulau Bangka yang menjorok ke laut lepas menjadikan teluk ini memiliki sejumlah aktivitas perikanan, aktivitas penambangan tepatnya Tambang Inkonvensional (TI) apung yang dikelola oleh masyarakat setempat. Penelitian bertujuan untuk mengidentifikasi jenis-jenis fitoplankton dan menganalisis indeks ekologi serta hubungan faktor fisika kimia perairan terhadap fitoplankton dan konsentrasi klorofil a di perairan Teluk Kelabat Luar. Penentuan lokasi penelitian ini menggunakan metode purposive sampling. Pengambilan sampel dilakukan secara tegak lurus kearah laut (horizontal) dengan menetapkan tiga titik sampling (ulangan) pada tiap stasiun dengan jarak 0, 1 dan 2 km. Berdasarkan hasil penelitian jenis fitoplankton yang paling banyak ditemukan adalah kelas Bacillariophyceae sebanyak 11 spesies dengan total 278 individu, Cyanophyceae 1 spesies dengan total 2 individu, kelas Chrysophyceae sebanyak 1 spesies dengan total 11 individu dan kelas Dinophyceae sebanyak 2 spesies dengan total 16 individu. Jenis fitoplankton yang memiliki jumlah individu terbanyak adalah Rhizosolenia robusta yang berjumlah 38 individu. Konsentrasi klorofil-a kisaran antara 0,0634 – 0,3014 mg/L. Indeks keanekaragaman fitoplankton di perairan Teluk Kelabat Luar termasuk dalam kategori sedang (1,881-2,204), indeks keseragaman tergolong tinggi (0,880-0,957) dan indeks dominansi tergolong rendah (0,116-0,172). Parameter fisika kimia perairan yang berpengaruh terhadap hubungan fitoplankton dan klorofil a meliputi suhu, pH, kecerahan dan salinitas. Kata kunci: fitoplankton; klorofil-a; Teluk Kelabat.